Relationship between perceived leadership styles and the intention to leave among customer service staff of a private company : the mediating role of job stress - Abdussalam, Hannat Tope Ahmad (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
This research will look at the relationship perceived between perceived leadership styles and intention to leave among customer service staff of private company as well as the mediating role of stress. One hundred and twenty seven employees who work in customer service from different private organizations were selected through convenient sampling to participate in the study. They were administered three questionnaires: 1) Multifactor Leadership Questionnaire, 2) General Work Stress Scale, and 3) Turnover Intent Scale from the Michigan Organizational Assessment Questionnaire. It was hypothesized that: a) transformational and transactional leadership styles will have significant relationships with job stress, b) transformational and transactional leadership styles will have significant relationships with the intention to leave, c) job stress will have a significant relationship with the intention to leave and d) job stress will mediate the relationship between leadership styles and the intention to leave. The questionnaires were administered either through email or by hand. The data collected was analyzed using SPSS version 21. The results showed that transformational and transactional leadership styles did not have a significant relationship with job stress. Transformational leadership styles showed no relationship with intention to leave, while transactional leadership styles were shown to have a significant relationship with the intention to leave. Job stress was seen to have a significant relationship with the intention to leave. No evidence of a direct or indirect mediation effect was seen between perceived leadership styles and the intention to leave.